On Oscillatory Solutions of Neutral Functional Differential Equations (Sebha University Conference Proceedings, 2025)
In this article, a specific neutral functional differential equations class is considered. Some new sufficient conditions related to the oscillatory solutions are constructed. These conditions extend and improve several well-known conditions in many existing studies.